Haematobiochemical alterations and lesion characterization induced by haemonchosis in slaughtered sheep at Gondar ELFORA abattoir, Ethiopia - Birhan Anagaw Malede; Mersha Chanie Kebede; Asnakew Mulaw Berihun; Muluken Yayeh Mekonnen; Mohammed Yesuf; Tadegegn Mitiku; Mastewal Birhan; Ambaye Kenubih; Abraham Belete Temesgen (BMC Veterinary Research)
Abstract Haemonchosis is a major gastrointestinal parasitic infection in sheep caused by H. contortus. An abattoir-based cross-sectional study was conducted from January to September 2024 to assess the haematobiochemical alterations and lesion characterization induced by haemonchosis in slaughtered sheep at Gondar ELFORA abattoir. The study involved 60 male local breed sheep, divided into 30 infected and 30 non-infected controls. The selection process involved postmortem examination of the abomasum tissues, incision, palpation, and visual inspection. Blood samples were taken for haematology and serum biochemical profiles, and a three cm tissue sample with typical H. contortus lesions was also taken. The study found significant reductions in hemoglobin, hematocrit, corpuscular volume, hemoglobin, and red blood cell counts in the infected group compared to the non-infected group. However, white blood cells, monocytes, neutrophils, and eosinophils were significantly higher in the infected group. Biochemical parameters showed significant reductions in total protein, albumin, globulin, and albumin-to-globulin ratio in the infected group. Erythrocyte indices indicated microcytic normochromic anemia. Gross examination revealed hemorrhages, dark brown abomasal contents, blood streaks, and a nodular lesion. Microscopic analysis revealed tissue-dwelling worms, submucosal hemorrhage, mucosal gland hyperplasia, thickened muscularis, and hyperplastic abomasal glands. The alterations in haematobiochemical parameters support the findings from gross and microscopic lesions. Thus, integrating haematobiochemical analysis with gross and microscopic lesion characterization improves the diagnosis of haemonchosis. Due to hypoproteinemia observed, it is advisable to supplement helminth-infected animals with protein-rich feeds, such as legumes.